WRAN을 위한 스펙트럼 센싱에 관한 연구 - 오상민; 임종태; Oh, Sang-Min; Lim, Jong-Tae (한국항행학회논문지, 2008)
Recently, many frequency sharing technology including CR (Cognitive Radio) technology have been studied actively because of frequency scarcity. For implementing CR systems, spectrum sensing technology plays key role. In IEEE 802.22 WRAN, the first standard aimed at Internet service in a TV channel with CR technology. This paper explained the various spectrum sensing schemes detecting narrowband ATSC signal in the IEEE 802.22 such as Energy detector, Spectral Correlation Sensing scheme, Covariance based Sensing algorithm and analyzed in terms of the probability of misdetection when the probability of false alarm is 10%. Based on simulation results, this paper proposed a duplex sensing scheme based on Energy detector and analyzed the capability of the proposed sensing scheme comparing with each sensing scheme. 최근 주파수 자원 부족 문제로 인하여 무선 인지(Cognitive Radio) 기술과 같은 주파수 공유 기술에 대한 연구가 활발히 진행 중에 있다. CR기술의 구현을 위해서는 주파수 대역의 사용 유무를 판단하는 스펙트럼 센싱기술의 구현이 우선시 된다. IEEE 802.22 WRAN은 CR 기술을 사용한 첫 번째 표준화로 TV대역에서의 인터넷 서비스를 목표로 하고 있다. 따라서 본 논문에서는 IEEE 802.22에 제시된 여러 센싱 기법들 중에서 협대역에서 ATSC신호를 검출하는 센싱 기법들인 에너지 검출기법, 스펙트럴 상관성 센싱 기법, 공분산을 이용한 센싱기법에 대하여 설명하고 오경보 확률이 10%일때의 미검출 확률을 통해서 성능을 분석하였다. 분석한 결과를 바탕으로 각각의 센싱 기법의 장단점을 보완할 수 있는 방법으로 에너지 검출 기법을 기반으로 하는 이중 센싱 구조를 제안하였고, 제안된 센싱구조를 실험을 통해 각각의 센싱 기법과 비교 분석하였다.